PENGEMBANGAN LKPD DISCOVERY LEARNING BERBANTUAN AUGMENTED REALITY PADA MATERI STRUKTUR ATOM - Azzahra, Anisa; Saputra, Andrian; Tania, Lisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning atomic structure is often constrained by the difficulty of visualizing abstract submicroscopic concepts, where 51.6% of students report a lack of interactive 3D media. This study aimed to develop Augmented Reality (AR)-assisted discovery learning student worksheets (LKPD) on atomic structure, and to evaluate their validity and practicality. The study employed a Research and Development (R&D) method adapting the Borg and Gall model limited to five stages: research and information collecting, planning, preliminary product development, preliminary field testing, and product revision. Research subjects included 93 students and 5 chemistry teachers during the needs analysis, 3 expert validators, and 2 chemistry teachers alongside 28 tenth-grade students (Class X.5) at SMAN 14 Bandar Lampung during preliminary field testing. Data were collected via questionnaires and analyzed using the Scale Content Validity Index/Average (S-CVI/Ave), Cronbach's Alpha, and percentage analysis. Results showed S-CVI/Ave scores of 0.94 for content appropriateness, 0.96 for construction, and 0.97 for readability and attractiveness, with Cronbach's Alpha > 0.70 (highly valid and reliable). Practicality evaluations yielded an average of 98.88% from teacher responses and 97.49% from student responses (very high category). Therefore, the AR-assisted discovery learning LKPD is proven to be valid and practical for use as an innovative chemistry instructional material.